2018
DOI: 10.1177/1071100718793567
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fixation Type and Bone Graft on Tarsometatarsal Fusion

Abstract: Level III, retrospective comparative study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 33 publications
2
30
1
1
Order By: Relevance
“…However, neither of these determinants was associated with a higher risk of nonunion or wound healing problems (P > .05). Buda et al 3 analyzed 88 patients after midfoot arthrodesis and did not identify a higher nonunion rate in obese patients or patients aged ≥60 years. However, they also detected an association between the number of columns treated and higher complication rates.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, neither of these determinants was associated with a higher risk of nonunion or wound healing problems (P > .05). Buda et al 3 analyzed 88 patients after midfoot arthrodesis and did not identify a higher nonunion rate in obese patients or patients aged ≥60 years. However, they also detected an association between the number of columns treated and higher complication rates.…”
Section: Discussionmentioning
confidence: 98%
“…To our knowledge, there is only one clinical study focusing on the fixation technique. 3 This study group identified isolated plate fixation as a risk factor for nonunion.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The author noted that locking plates combined with a compression screw presented a favorable tension-side implant location that closed the fusion site under load. In a recent study, Buda et al [ 30 ] compared the nonunion complications in 88 patients (189 joints) who underwent first cuneometatarsal joint fusion. The fixations were made using three different fastening systems: with a plate only, with screws only, and with hybrid construction using plate and screws.…”
Section: Discussionmentioning
confidence: 99%
“…Für Lisfranc-Arthrodesen liegen die Raten noch ein wenig höher, je nach Patientenkollektiv, zwischen 7 und 11 % [24]. Buda et al konnten in ihrem Kollektiv nachweisen, dass für die Lisfranc-Arthrodesen die Verwendung einer Kombination von Kompressionsschrauben und Platten sowie die Anlage von autologer Spongiosa erhöhte Fusionsraten mit sich brachte [24].…”
Section: Pseudarthrosen Bei Arthrodesen Im Bereich Des Fußesunclassified